LAW STUDENT PROJECT: PEMBERDAYAAN KOMUNITAS PELUKIS DAERAH PEJATEN BARAT TERHADAP PERLINDUNGAN HAK CIPTA DAN PENDAFTARAN CIPTAAN SENI LUKIS - Simanjuntak, Anni Alvionita; Fauzan, Muhammad; Saffanah, Arla Haiqa; Reza, Muhammad (Zhata Institut, 2024)
Community service is one of the pillars of the Tri Dharma of Higher Education which must be implemented. Lecturers and students at the Faculty of Law, National Development University